Comparative study of Japanese nationwide epidemiological studies of myasthenia gravis using datasets of 2006 and 2018 - Hiroaki Yoshikawa; Yumi Adachi; Yosikazu Nakamura; Nagato Kuriyama; Hiroyuki Murai; Yoshiko Nomura; Yasunari Sakai; Kazuo Iwasa; Yutaka Furukawa; Makoto Matsui; Satoshi Kuwabara (PLoS ONE, 2025)
Objective This study aimed to identify changes in the clinical presentation and treatment patterns of myasthenia gravis (MG) in Japan by comparing data from nationwide epidemiological surveys conducted in 2006 and 2018. Methods We analyzed data from nationwide epidemiological surveys of MG performed across Japan in 2006 (n = 729) and 2018 (n = 1,357). Both surveys adhered to the Survey Manual of Study on Continuous Epidemiological Data Collection of Intractable Diseases established by the Ministry of Health, Labour, and Welfare. We compared the following variables between the two-time points: age of onset, gender distribution, initial symptoms, anti-acetylcholine receptor antibody (AChRAb) status, physiological test results (repetitive nerve stimulation test, edrophonium test), Myasthenia Gravis Foundation of America (MGFA) Clinical Classification, Myasthenia Gravis Activities of Daily Living Profile (MG-ADL) score, and treatment modalities. Results Our analysis revealed a significantly older age of onset in the 2018 cohort compared to 2006. The MGFA Clinical Classification was higher in 2018, and bulbar weakness was more frequently reported as an initial symptom. Conversely, the occurrence of myasthenic crisis and current MG-ADL scores were lower in 2018. Regarding treatment, the utilization of tacrolimus, plasma exchange (PE), and intravenous immunoglobulin (IVIg) significantly increased between 2006 and 2018. In contrast, the rates of thymectomy and both maximum and current oral steroid dosages decreased during this period. Conclusion These findings underscore notable shifts in the clinical characteristics and, particularly, the treatment strategies for MG in Japan over the twelve-year interval. This information is crucial for informing future patient care protocols and healthcare policy development in the management of MG. We emphasize the importance of conducting regular nationwide epidemiological surveys to monitor the evolving landscape of MG and its treatment continuously.